Turning Attention Inwards: Seventeenth-Century Poetry of Interoception - Uribe Bracho, Lorena (Intermédialités / Intermediality)

(untitled) (Revue intermédialités, 2024)
“Interoception,” a term that has attracted a significant amount of attention over the past few years, refers broadly to the ability to sense what goes on inside the body: the rhythm of circulation, pangs of hunger, breathing patterns, fluctuations in mood, the movements of a child in the womb, and countless other processes with different levels of accessibility to the conscious mind.This article claims that attention to the inside of the body is a vital part of the experience of poetry in early modern times and that poetic language can be a key part of the cultural training that shapes the perception of visceral landscapes. The discussion follows the lead of several shared traits between poetry and interoception, including rhythmic patterning, intermittence, strong experiential potential, predictive processing, and cumulative effects. For this purpose, it draws from recent work in the field of cognitive science, and also from lyric theory, work on poetic form, and a range of texts on early modern poetry, history, and culture.The argument for a “poetry of interoception” is tied to the idea that a number of cultural factors align in the seventeenth century and sharpen the interest in the inside of the body as changing medical paradigms meet the old vehicle for attention to subjectivity that is the lyric mode. These factors operate across Europe and Colonial America, and thus the poems that are used as examples belong to different languages and national traditions.